Determinants of Health Literacy Regarding Breast Cancer Based on the Health Belief Model Framework in North Sumatra - Kalvin Ginting; Elyani Sembiring; Ziska Herawaty (Lembaga Publikasi Ilmiah Nusantara, 2026)
Breast cancer remains a major public health problem among women in Indonesia, including North Sumatra, where limited health literacy may contribute to delayed diagnosis and low participation in early detection. This study aimed to analyze the determinants of breast cancer health literacy based on the Health Belief Model framework among women in North Sumatra. A quantitative cross-sectional study was conducted involving 250 women selected through purposive sampling. Data were collected using a structured questionnaire measuring breast cancer health literacy and Health Belief Model constructs, including perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. Data were analyzed using descriptive statistics, bivariate analysis, and multivariate logistic regression. The findings showed that most respondents had moderate breast cancer health literacy. All Health Belief Model constructs were significantly associated with health literacy, with self-efficacy identified as the strongest determinant, followed by perceived benefits. Perceived barriers negatively influenced women’s ability to access and apply breast cancer-related information. These findings indicate that breast cancer health literacy is shaped not only by knowledge and education but also by psychosocial perceptions and sociocultural conditions. Strengthening women’s self-efficacy and reducing perceived barriers should be prioritized in culturally sensitive breast cancer education and early detection programs in North Sumatra.